2014
DOI: 10.1039/c3cp54470b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromophore encapsulation on linear and nonlinear optical properties: the case of “miniSOG”, a protein-encased flavin

Abstract: Linear and nonlinear spectroscopic parameters of flavin mononucleotide, FMN, have been examined both experimentally and computationally under conditions in which FMN is (1) solvated in a buffered aqueous solution, and (2) encased in a protein that is likewise solvated in a buffered aqueous solution. The latter was achieved using "miniSOG" which is an FMN-containing protein engineered from Arabidopsis thaliana phototropin 2. Although it is reasonable to expect that the encasing protein could have an appreciable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 70 publications
6
57
1
Order By: Relevance
“…In the previous section, we have shown that the first two bright states from ADC(2), CC2, and CAM‐B3LYP calculations involve π H → π * L and π H‐1 → π * L transitions, and their positions are found in qualitative agreement with the experimental peaks (Table ). However, the gas‐phase results are blueshifted with respect to the absorption peaks of lumiflavin measured in water and within the protein embedded system . Our recorded spectrum in chloroform is shown in Figure that is consistent to the previous experimental studies by Sikorski et al .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In the previous section, we have shown that the first two bright states from ADC(2), CC2, and CAM‐B3LYP calculations involve π H → π * L and π H‐1 → π * L transitions, and their positions are found in qualitative agreement with the experimental peaks (Table ). However, the gas‐phase results are blueshifted with respect to the absorption peaks of lumiflavin measured in water and within the protein embedded system . Our recorded spectrum in chloroform is shown in Figure that is consistent to the previous experimental studies by Sikorski et al .…”
Section: Resultssupporting
confidence: 91%
“…Also the long-range corrected functional CAM-B3LYP can give accurate description for state ordering among the low-lying excited states. This has been shown for double-zeta basis set by List et al (73) as well as triple-zeta basis set in Table 2. The fact that CAM-B3LYP is adjusting the energetic order indicates a partial charge transfer character of the S 4 state which is not correctly described using B3LYP.…”
Section: Assessment Of Vertical Excitation Energies Of Lumiflavinsupporting
confidence: 57%
See 2 more Smart Citations
“…It has been successfully applied to model the environmental effects on both electric and magnetic molecular properties. 8,27,28 The aim of the present study is to broaden the scope of the PE model to vibrational properties of molecules embedded in large and complex environments. To this end, we have implemented molecular gradients with respect to nuclear displacements in the quantum region within the PE framework.…”
Section: Introductionmentioning
confidence: 99%